GAYA BAHASA KIASAN DALAM WACANA IKLAN JEPANG - Putri, Meira Anggia (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2015)
Japan is the land of industry which produces many kind of products. To market their product one of the effective ways is by using advertisement. Advertisement is something that we always see in our daily life. We can find it anywhere, at the billboard, television, magazine, newspaper, radio, etc. Since the objective of any type of advertising is to persuade the public to buy product or service, advertiser uses many ways to convey his product message, one of them is by using figurative language. Figurative language is language that is used in an exaggerated fashion to represent an idea. Figurative language in advertising is used to help the consumer picture himself benefiting from the product or service being mentioned. Based on Abrams theory, figurative language divided into two classes: figures of thought and figures of speech. Figures of thought grouped into five, they are simile, metaphor, metonymy, synecdoche, and personification. Japanese advertisers often use this figures of thought to their ads. This paper discusses about figures of thought in Japanese ad copywriting. The purpose of this paper is to analyze the use of figures of thought in Japanese ad Copywriting for knowing the message it contains.Keywords: Japanese advertising, copywriting, figurative language, figures of thought.